Pemanfaatan Botol Bekas Sebagai Wadah Akuaskap Ikan Hias Di Tk Aisyiyah Bustan Athfal Jampue Kabupaten Pinrang - Ummu Kaltsum SC; Nurul Mutmainnah; Yusdalifah Ekayanti Yunus; Sri Nur Qadri (PPPM POLITEKNIK NEGERI SAMBAS, 2023)
Plastic bottle waste is the result of waste in the form of bottles made of plastic or glass resulting from a production process both industrial and domestic. The existence of this waste is considered to have no economic value and selling value, but to reduce the abundance of plastic waste, especially plastic bottles, there must be innovation that has the purpose of utilization. The concept of using plastic bottle waste as a medium for maintaining ornamental fish is called Aquascape. This activity was carried out in November 2022. One of the methods carried out was by introducing students to recycling plastic bottles and types of ornamental fish. It is hoped that this dedication will reduce the capacity of plastic waste which can reduce the quality of health and the beauty of the environment. The results of collecting used bottles will later be created into an aquascape.